Principles and applications of narrowband internet of things (NBIoT) - Routray, Sudhir K., 1977-; Mohanty, Sasmita, 1986- (Advances in wireless technologies and telecommunication (AWTT) book series., 2021)
"This book explores recent advances in Narrowband Internet of Things (NB-IoT), its architecture, deployment issues, and its applications"--